2017
DOI: 10.1136/bmjquality.u220946.w7041
|View full text |Cite
|
Sign up to set email alerts
|

Using real-time, anonymous staff feedback to improve staff experience and engagement

Abstract: Improving staff engagement has become a priority for NHS leaders, although efforts in this area vary between organisations. University Hospital Bristol NHS Foundation Trust (UH Bristol) is a tertiary teaching hospital where concerns about staff satisfaction and communication were reflected in the 2014 staff survey. To improve staff engagement, a real-time feedback mechanism to capture staff experience and to facilitate feedback from local leaders, was developed and piloted using the Model for Improvement. Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…A number of comparisons can be made between our study and those of Frampton et al 18 and Hinsley et al 17 As with our study, both studies developed the tool in collaboration with hospital personnel. Both studies used a simple visual system, smiley face and traffic light, and aimed to gain additional information regarding the reasons underpinning staff responses.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A number of comparisons can be made between our study and those of Frampton et al 18 and Hinsley et al 17 As with our study, both studies developed the tool in collaboration with hospital personnel. Both studies used a simple visual system, smiley face and traffic light, and aimed to gain additional information regarding the reasons underpinning staff responses.…”
Section: Discussionmentioning
confidence: 71%
“…Transparent and regular feedback and action from managers are likely to be essential for the tool's success, with trust likely to develop as staff see evidence of positive change through its use. This was a seen in both the Frampton et al 18 and Hinsley et al 17 studies, which were conducted over much longer time frames. Both studies reported an increase in staff engagement as management actively and positively responded to feedback and comments.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As incorporation of performance metric reports in the feedback process has not yet become standardized at our institution, it is not surprising that resident physicians felt anxiety about the process. Prior studies have demonstrated a need for improved quantitative feedback provided to residents beyond the milestone scores and a recent study found that feedback can improve patient safety culture and lower burnout rates . Performance metric reports provide an opportunity to integrate data from the EHR and augment feedback from the competencies patient flow and system‐based management to improve feedback opportunities for our learners.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with feedback has been linked to improvements in staff motivation, satisfaction with level of responsibility and involvement, and perceived support from managers . Providing feedback has also been shown to lower rates of burnout, increase employee engagement, and improve patient safety culture .…”
mentioning
confidence: 99%